The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/adem.201901198
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Cleaning Mucus‐like and Hierarchical Ciliary Bionic Surface for Marine Antifouling

Abstract: The flexible mucus film and hydrophilic hierarchical micro‐/nanoprotuberance structure on the skin surfaces of marine organisms contribute to an excellent intrinsic antifouling performance. Inspired by this fact, a self‐cleaning mucus‐like and hierarchical ciliary bionic antifouling surface (SMCAS) is designed for marine antifouling based on the electrostatic flocking technology. The results of scanning electron microscopy (SEM) show that the bioinspired SMCAS has a hierarchical micro‐/nanociliary structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…because of high teratogenicity, ecofriendly, and efficient marine antifouling coatings are still extensively studied to this day. [4,5] Many antifouling coatings have been developed in this battle against marine fouling, such as self-polishing coating, [6][7][8] low surface energy (SE) coating, [9][10][11][12] micro-structured coating, [13][14][15] hydrophilic coating, [4,16,17] hydrophobic coating, [18][19][20][21] amphiphilic coating, [7,8,22] antifoulant release coating, [9,23] dynamic biodegradable coating, [16,24,25] slippery liquid-infused porous surface (SLIPS), [26][27][28][29][30] bactericidal coating, [23,31] mimic peptide coating, [32] fluorescent coating, [33] and so on. Among these methods, SLIPS has attracted continuous attention because of low SE, low Young's modulus, and dynamic antifouling surface.…”
mentioning
confidence: 99%
“…because of high teratogenicity, ecofriendly, and efficient marine antifouling coatings are still extensively studied to this day. [4,5] Many antifouling coatings have been developed in this battle against marine fouling, such as self-polishing coating, [6][7][8] low surface energy (SE) coating, [9][10][11][12] micro-structured coating, [13][14][15] hydrophilic coating, [4,16,17] hydrophobic coating, [18][19][20][21] amphiphilic coating, [7,8,22] antifoulant release coating, [9,23] dynamic biodegradable coating, [16,24,25] slippery liquid-infused porous surface (SLIPS), [26][27][28][29][30] bactericidal coating, [23,31] mimic peptide coating, [32] fluorescent coating, [33] and so on. Among these methods, SLIPS has attracted continuous attention because of low SE, low Young's modulus, and dynamic antifouling surface.…”
mentioning
confidence: 99%
“…Many of these have taken inspiration from nature and have incorporated aspects of sharkskin; crustaceans; or, more recently, mucus generation and hydrophilic hierarchical micro/nano-structures found on marine organisms [ 63 ]. Ren et al have recently reported “mucus-like and hierarchical ciliary bionic” antifouling surfaces for marine antifouling applications [ 63 ]. Another group have used snail shells exhibiting oleophobic properties and a surface texture [ 64 ] to explore the feasibility of recreating similar structures on the inner surfaces of conventional biliary stents for antifouling purposes in medical fields [ 65 ].…”
Section: Biomimetic Antifouling Strategiesmentioning
confidence: 99%
“…Multiple commercial applications have considered this approach, with some promising technologies in development or at commercial stage (see for example Finsulate: www.finsulate.com-accessed on 1 May 2020). Many of these have taken inspiration from nature and have incorporated aspects of sharkskin; crustaceans; or, more recently, mucus generation and hydrophilic hierarchical micro/nano-structures found on marine organisms [63]. Ren et al have recently reported "mucus-like and hierarchical ciliary bionic" antifouling surfaces for marine antifouling applications [63].…”
Section: Surface Texture Control and Biomimeticsmentioning
confidence: 99%
“…Bioinspired surfaces with microscale or nanoscale structures have widespread applications because of their unique properties, for example, self-cleaning, , energy harvesting, thermal management, , radiative cooling, , drag reduction, , and reversible adhesion . The droplets deposited on the lotus leaf or rose petal both exhibit a high contact angle (>150°).…”
Section: Introductionmentioning
confidence: 99%